Reseña del libro: Marqueta, B., López-Cortés, N. y Ariño-Bizarro, A. (2022) (eds.). Avances de la Lingüística y su aplicación didáctica - Nerea Marco Reus (Estudios de Lingüística)
Marqueta, Bárbara, López-Cortés, Natalia y Ariño-Bizarro, Andrea (eds) (2022). Avances de la Lingüística y su aplicación didáctica. AKAL. 256 páginas. ISBN: 978-84-460-5186-2.